CORALINE’S DREAM REPRESENTED IN CORALINE MOVIE BASED ON CARL JUNG’S DREAM THEORY - LAILY, MEY FIKA NIKMATU (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: conscious, dream, collective unconscious, archetype, individuationDream is a daily phenomenon which is experienced by human being. Coraline movie is adapted from a novel with the same title. It tells about a child named Coraline who feels neglected by her mother and she reveals the repressed feeling in her dream.Carl Jung’s dream theory is applied in Coraline movie to points out the dream through the character’s individual psyche. In this case, dream theory is used to identify the imbalance both unconscious and conscious of the people’s psyche which express and appear on the dream. Dream also expresses both the collective unconscious and archetypes. The  research employs  psychological  approach  in  order  to  serve  more information focused on  the  subject  being  studied.  This approach directs the discussion to use psychology theory to analyze and interpret the data in the Coraline movie that is Coraline’s dream.Coraline’s unconscious that is expressed in a dream depicts of an angel-parents who always care and give full attention to her. Mother archetype also appears in a dream that represents as a witch. The result of the study shows about the unconscious that was expressed in Coraline’s dream is indicated a solution through a symbol. Coraline realizes and approves that life with the parents in real world is better and more beautiful than the other mother as in dream. The balance of unconscious and conscious was needed to achieve the individuation.